Student Sleep Quality during a Pandemic and its Relationship with Smartphone Use Intensity - Honanda, Michelle Vanya; Arianti, Rudangta (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Sleep is a basic human need that must be met, but pandemic can cause various changes on many aspects. One of the changes including the use of smartphones. Excessive use of smartphones will make individuals experience a decreased of sleep quality. This study aims to determine the correlation between smartphone usage intensity and sleep quality during pandemic. Sleep quality data was collected using Pittsburgh Sleep Quality Index (PSQI), while smartphone usage intensity data was collected using smartphone usage intensity scale. Participants in this study were 225 undergraduate psychology students at Satya Wacana Christian University. Hypothesis test was analyzed by Spearman Rank Techniques with a coefficient of -0,208 with a significance value of 0,001 (p<0,05). The result in this study indicates that there is a negative correlation between smartphone usage intensity and sleep quality which indicates that if the student’s smartphone usage intensity is increased, then the student’s sleep quality will be decreased.Tidur merupakan kebutuhan dasar manusia yang harus terpenuhi, namun kondisi pandemi dapat menyebabkan berbagai perubahan dalam dalam berbagai aspek. Salah satu perubahan tersebut termasuk dalam penggunaan smartphone. Penggunaan smartphone yang berlebihan tersebut akan membuat individu mengalami penurunan kualitas tidur. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan smartphone dengan kualitas tidur mahasiswa di masa pandemi. Pengambilan data kualitas tidur menggunakan Pittsburgh Sleep Quality Index (PSQI) sedangkan pengambilan data intensitas penggunaan smartphone menggunakan skala intensitas penggunaan smartphone. Partisipan dalam penelitian ini adalah 225 mahasiswa S1 Fakultas Psikologi Universitas Kristen Satya Wacana. Uji hipotesis dilakukan dengan menggunakan teknik korelasi rank spearman dengan hasil koefisien sebesar -0,208 dan nilai signifikansi 0,001 (p<0,05). Hasil penelitian ini menunjukkan bahwa terdapat hubungan negatif antara intensitas penggunaan smartphone dengan kualitas tidur yang menunjukkan bahwa jika semakin tinggi intensitas penggunaan smartphone maka semakin rendah kualitas tidur yang dimliki.